Platinum on Nanodiamond: A Promising Prodrug Conjugated with Stealth Polyglycerol, Targeting Peptide and Acid‐Responsive Antitumor Drug. (23rd May 2014) - Zhao, Li; Xu, Yong‐Hong; Qin, Hongmei; Abe, Shigeaki; Akasaka, Tsukasa; Chano, Tokuhiro; Watari, Fumio; Kimura, Takahide; Komatsu, Naoki; Chen, Xiao
<x xml:space="preserve">Abstract</x> In the field of nanomedicine, nanoparticles with various functions are required for in vivo applications such as biomedical imaging and drug delivery. Therefore, chemical functionalization of nanoparticles has been extensively investigated. Herein, nanodiamond (ND) coated with polyglycerol (PG) and its derivatives is reported to impart good solubility in a physiological environment, a stealth nature to avoid nonspecific uptake, a targeting property to be taken up by a specific cell, and an acid‐responsive drug release property to kill cancer cells. ND is first grafted with PG and the resulting ND‐PG has a high solubility in physiological media. Since a large number of hydroxyl groups in PG provide scaffolds for further surface functionalization, the targeting RGD peptide and Pt‐based drug are immobilized to give ND‐PG‐RGD, ND‐PG‐Pt and ND‐PG‐RGD‐Pt. The ND with intrinsic fluorescence is also functionalized by PG and RGD to confirm cellular uptake and intracellular localization fluorescently. The results of the cell experiments indicate that PG coating shielded fND from the uptake by HeLa and U87MG cells. In contrast, fND‐PG‐RGD is taken up by U87MG, not HeLa cells, exhibiting high targeting efficacy. When ND‐PG‐RGD‐Pt is applied, U87MG is selectively killed against HeLa. The multi‐functional ND is a promising prodrug in targeting chemotherapy.